Promoting spiritual ideals through design thinking in public schools - Tan, Charlene (International journal of children's spirituality, 2012)
Against a backdrop of the debates on religious education in public or state schools, we argue for the introduction of spiritual ideals into the public school curriculum. We distinguish our notion of spiritual ideals from religious ideals as conceptualised by De Ruyter and Merry. While we agree with De Ruyter and Merry that ideas drawn from religious/spiritual sources play a significant role in the students’ identity formation, development into reasonable liberal democratic citizens, and flourishing as adults, we highlight some problems with their conception of religious ideals. Instead of religious ideals, we propose spiritual ideals in schools using a design thinking approach that acknowledges and welcomes the students’ diversity in understandings of spirituality. We further give examples of student projects that illustrate the potential of design thinking as a pedagogical tool for students to acquire spiritual ideals.